Simultaneous Determination of Carvedilol and Hydrochlorothiazide in Tablets by Derivative Spectrophotometric and HPLC Methods - SULTAN, MAHA (Asian Journal of Chemistry, 2010)
Two new simple and selective assay methods have been presented for the resolution and determination of the binary mixtures of carvedilol (CRV) and hydrochlorothiazide (HCTZ) in pharmaceutical formulations. The first method depends on first derivative ultraviolet spectrophotometry (1D) with zero-crossing technique of measurements at 248 and 285 nm for CRV and HCTZ, respectively. The assay was linear over the concentration ranges 0.05-1.5 μg mL-1 for CRV and 0.5 - 15 μg mL-1 for HCTZ. The determination limit for CRV and HCTZ were found to be 0.025 and 0.25 μg mL-1, respectively; while the detection limit were 0.005 μg mL-1 for CRV and 0.1 μg mL-1 for HCTZ. The second method was based on isocratic reversed-phase liquid chromatography (HPLC) on Nucleosil LC18 column (25 cm × 4.6 mm), using a mobile phase acetonitrile- 10 mM potassium dihydrogen phosphate (pH 3.0), (30:70 v/v) at flow rate of 1 mL/min. Losartan was used as an internal standard and the substances were detected at 230 nm. The linearity range were 0.05- 1.00 and 0.1-1.0 μg mL-1 for CRV and HCTZ, respectively. The determination and detection limit were found to be 0.02 and 0.005 μg mL-1 for CRV and 0.05 and 0.01 μg mL-1 for HCTZ, respectively. The proposed methods were successfully applied for the determination of these drugs in synthetic mixtures and commercially available tablets. The results were compared statistically at 95 % confidence level with each other. There was no significant difference between the mean percentage recoveries and precision of the two methods.